Profile of cardiovascular disease risk in type 2 diabetes mellitus patients receiving statin therapy: A cross-sectional study - Yasmin Karimah Ikhsan, Yasmin
Abstract Background: Cardiovascular disease is still the number 1 cause of death globally. Meanwhile, type 2 diabetes mellitus (T2DM) is a risk factor for atherosclerosis vascular disease (ASCVD), so an assessment using Framingham Risk Score (FRS) is needed to predict the risk of ASCVD in the future.